2016
DOI: 10.1071/he16013
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of alcohol supply to children – associations with adults’ own age of initiation and social norms

Abstract: Issue addressed The aim of this study was to investigate predictors of adults’ perceived acceptability of introducing alcohol to children less than 18 years of age. Methods An online survey. Logistic regression analyses were used to examine the association between demographic characteristics, alcohol consumption, and social norms and adults’ own age of initiation. Results Alcohol consumption, age of initiation and perception of the acceptability of drunkenness were all correlated with the acceptability of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Further, there is a commonly‐held belief that supervised alcohol consumption is an effective harm‐minimisation strategy . Consistent with this, studies in Australia , New Zealand and the UK have found that the age at which it is perceived acceptable for children to have a full drink of alcohol is around 17 years—a year earlier than the legal purchase age (but often perceived to be a legal drinking age) of 18—and a weak or watered down drink 1 to 2 years earlier than this. Strategies to correct misperceptions of social norms have been effective in reducing alcohol consumption among young drinkers , and it is possible that similar strategies could be effective in reducing parents’ intentions to supply.…”
Section: Introductionmentioning
confidence: 81%
“…Further, there is a commonly‐held belief that supervised alcohol consumption is an effective harm‐minimisation strategy . Consistent with this, studies in Australia , New Zealand and the UK have found that the age at which it is perceived acceptable for children to have a full drink of alcohol is around 17 years—a year earlier than the legal purchase age (but often perceived to be a legal drinking age) of 18—and a weak or watered down drink 1 to 2 years earlier than this. Strategies to correct misperceptions of social norms have been effective in reducing alcohol consumption among young drinkers , and it is possible that similar strategies could be effective in reducing parents’ intentions to supply.…”
Section: Introductionmentioning
confidence: 81%
“…Drinking initiation is a result of a combination of contextual factors including parental drinking, parental supervision, friends’ drinking, and school bonding [ 16 ]. Apart from those who are likely to drink heavily themselves, parents with early onset of drinking perceived providing alcohol to children as acceptable [ 36 ]. Hence, an effect of earlier drinking initiation in one generation may lead to HED in the next generation.…”
Section: Discussionmentioning
confidence: 99%